Transmedia Political Journalism. Strategies for the Development of the Profession in the Current Media Ecosystem - Robledo Dioses, Kelly (2016)
Through time, Journalism has faced changes about the emergence of new Media, but this process also involves issues of narrative and new audience management. So, adapting to the new environment becomes in a necessity, and specifically in political journalism is where it becomes more evident, because the type of information transmitted has great value to society. In this way, this research shows to transmedia storytelling as the best ally of journalism today for the distribution of news, especially political news. This communication model, because of his spreadability, multiplicity and drillability nature, will raise the level of audience participation in each media that transmit the newsworthy event.